Nitrogen, irrigation, and alley management affects raspberry crop response and soil nitrogen and root‐lesion nematode dynamics. Issue 4 (28th May 2021) - Kuchta, Shawn; Neilsen, Denise; Zebarth, Bernie J.; Forge, Tom; Nichol, Craig
Abstract: There is a need to improve raspberry crop nitrogen (N) management practices, particularly when grown over aquifers vulnerable to nitrate (NO3 ) leaching. This study quantified the effects of N, irrigation and alley management strategies on berry yield, indices of crop vigor and N status, growing season soil N dynamics, and root‐lesion nematode (RLN) population dynamics under red raspberry production in British Columbia, Canada. Conventional management (100 kg N ha −1 surface broadcast on the row, clean cultivation of alleys, and drip irrigation for a fixed duration regardless of evapotranspiration [ET]) was compared with different mineral fertilizer N rates, application of N as manure, seeding the alley to either a perennial forage grass (perennial ryegrass [ Lolium perenne L.] and 'Bridgeport II' chewings fescue [ Festuca rubra subsp. commutate]) or an autumn‐seeded spring barley crop, or ET‐scheduled irrigation. In addition, the combination of ET‐scheduled irrigation plus fertigation of a reduced rate of N was compared with conventional practices at a reduced N rate. There was little or no crop response to N source and rate, a finding attributed primarily to high nonmanaged N inputs, and possibly also to RLNs present at population densities (grand mean = 4 per cm 3 soil) expected to suppress raspberry growth. ET‐scheduled irrigation reduced water use ∼50% compared with fixed‐duration irrigation without compromising crop performance. The perennial forage grass in the alley reduced soil mineral N but not yield. Taken together, these findings demonstrate that more environmentally sustainable raspberry production can be achieved through integrated management systems even in soils vulnerable to NO3 leaching. Core Ideas: Crop response to N source and rate was limited but manure increased soil mineral N. ET‐scheduled irrigation reduced water use ∼50% without compromising crop performance. Noncompetitive perennial alley cover crop reduced soil mineral N but not yield. More sustainable raspberry production can be achieved through integrated management.